2022
DOI: 10.1007/s00345-022-04178-x
|View full text |Cite
|
Sign up to set email alerts
|

Nonpapillary prone endoscopic combined intrarenal surgery: effectiveness, safety and tips, and tricks

Abstract: Purpose To evaluate the effectiveness and safety of nonpapillary prone endoscopic combined intrarenal surgery (ECIRS) and provide practical tips and tricks for the successful accomplishment of the procedure respecting the anatomical particularities. Material and methods This study is an analysis of a prospectively collected database including all cases of ECIRS performed between January 2019 and December 2021 in a high-volume tertiary center. All patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Otsuka et al [19 ▪ ] compared a lateral decubitus position with GMSV in 226 patients and reported that both operative time (92 vs. 189 s; P < 0.001) and fluoroscopic time was significantly shorter in the lateral decubitus position. Kallidonis et al [2 ▪ ] studied outcomes in 33 patients who had in purely prone position a nonpapillary prone ECIRS. By virtue of in-situ visualization of the puncture, it was reported as effective and well tolerated procedure.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Otsuka et al [19 ▪ ] compared a lateral decubitus position with GMSV in 226 patients and reported that both operative time (92 vs. 189 s; P < 0.001) and fluoroscopic time was significantly shorter in the lateral decubitus position. Kallidonis et al [2 ▪ ] studied outcomes in 33 patients who had in purely prone position a nonpapillary prone ECIRS. By virtue of in-situ visualization of the puncture, it was reported as effective and well tolerated procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining 162 full-text articles were further evaluated for appropriateness and 127 articles were excluded. Finally, 35 articles were considered eligible and included [1,2 ▪ ,6–13,14 ▪ ,15–17,18 ▪▪ ,19 ▪ ,20–22,23 ▪▪ ,24,25 ▪▪ ,26–36,37 ▪ ,38]. Figure 1 shows the flow diagram of the literature search.…”
Section: Evidence Synthesismentioning
confidence: 99%
See 3 more Smart Citations